TRADIITIONAL AND COMTEMPORARY PERCEPTION OF MULTIMEDIALITY A INTERACTIVITY - Milan, KLEMENT; DOSTÁL, Jiří (Trends in education, 2013)
The use of computers and of the Internet in education is a widely discussed topic, not only in the teaching community. The use of these devices manifests itself in the development of multimediality and interactivity. The concepts of multimediality and interactivity are not new and they have their predecessors in both pedagogical theory and practice. Multimediality can be understood as the fulfillment of the principle of clarity, which was formulated as early as by Comenius. Likewise, interactivity is based on the need of communication and interaction in training.However, modern information and communication technologies allow broader application of these principles, because multimediality and interactivity are endowed with features that can significantly predetermine the quality of education. It is also possible to observe some significant differences in traditional and contemporary understanding of these concepts. Some of the most important differences, defined on the basis of theoretical analysis, are introduced by the submitted essay
Keywords: multimediality; interactivity; education paradigms; concepts of the use of the computer in teaching process; information and communication technologies; clarity